Limitación al principio de mínima intervención penal en la conciliación en los delitos contra la propiedad. - Gualpa, Marco P. (2022)
The Ecuadorian State has a criminal prosecution system that guarantees the application of fundamental rights, considering that the principle of minimal criminal intervention implies a fragmentary and subsidiary right, in accordance with article 195 of the Constitution of the Republic of Ecuador and article 3 of the Code Comprehensive Penal Organic; however, the aforementioned principle is legitimized only when necessary, constituting the last resort, not applying extra-penal mechanisms. The Organic Code of the Judicial Function in article 130 numeral 11, orders the judge to seek conciliation, in cases in which the law does not provide otherwise, the Organic Comprehensive Criminal Code in article 663 numeral 3, establishes that to deal with a conciliation regarding crimes against property the amount of the protected legal asset cannot exceed thirty unified basic wages of the worker in general, causing the limitation to the principle of minimum intervention; As a general objective, a critical legal analysis was developed on the limitation to the principle of minimum intervention in access to conciliation in crimes against property; applying the mixed approach (qualitative - quantitative), with which we proceed to the collection and analysis of data based on statistical numerical measurement that allowed establishing guidelines and verifying the existing problem, the descriptive approach specified properties, important characteristics of the analyzed topic , the explanatory approach that allowed through the survey to establish the reason for the limitation of the principle of minimum intervention, strengthening, determining and fulfilling the general objective set; Likewise, the application of the inductive method which allowed the development of a critical legal analysis regarding the limitation to the principle of minimum intervention in access to conciliation in crimes against property, to finally conclude that there is indeed a limitation to the principle of minimal criminal intervention in access to conciliation in crimes against property, successfully developing critical legal analysis.